Exploration of Optical Properties of Novel Pyrene Derivatives Modified by Click Functionalization - Yang Yu; Yuzhen Zhao; Yongsheng Mi; Yang Zhao; Zhun Guo; Huimin Zhang; Dong Wang; Zongcheng Miao (Crystals, 2022)
A simple synthetic method was designed, in which the Sonogashira coupling reaction and [2+2] cycloaddition click reaction with high yield were performed on 1-bromopyrene to obtain several novel pyrene derivatives. The structure of each sample was characterized by Nuclear Magnetic Resonance (NMR), Mass Spectrometry (MS), Fourier transform infrared (FTIR) and elemental analysis. The characterization of the products by Ultraviolet-visible (UV-vis) and Photoluminescence (PL) spectroscopy proves that the addition of click groups has an important effect on the optoelectronic properties of pyrene derivatives. The Z-scan technique was used to test the third-order nonlinear optical (NLO) properties of the samples, and it could be found that the NLO properties of the products were improved and the transition of saturable absorption and reverse saturable absorption occurred with the addition of click reagent. These factors indicate that the click-modified pyrene derivatives have potential applications in areas such as optical limiting.